2017
DOI: 10.1155/2017/6528956
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Representation Based Range-Doppler Processing for Integrated OFDM Radar-Communication Networks

Abstract: In an integrated radar-communication network, multiuser access techniques with minimal performance degradation and without range-Doppler ambiguities are required, especially in a dense user environment. In this paper, a multiuser access scheme with random subcarrier allocation mechanism is proposed for orthogonal frequency division multiplexing (OFDM) based integrated radar-communication networks. The expression of modulation Symbol-Domain method combined with sparse representation (SR) for range-Doppler estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In order to implement a processor for the estimation of delay and Doppler frequency, the transmitted information has to be removed from the surveillance channel firstly. In OFDM-based passive radar, the reference signal includes a direct path signal and multipath signals, and the clean reference signal can be obtained by reconstruction [25]. Therefore, the transmitted signal…”
Section: Mth Nthmentioning
confidence: 99%
“…In order to implement a processor for the estimation of delay and Doppler frequency, the transmitted information has to be removed from the surveillance channel firstly. In OFDM-based passive radar, the reference signal includes a direct path signal and multipath signals, and the clean reference signal can be obtained by reconstruction [25]. Therefore, the transmitted signal…”
Section: Mth Nthmentioning
confidence: 99%
“…ExtractÛ to get E 1R , E 2R , E 1v , and E 2v in Equations ( 39) and (40) 45) and (46), then perform diagonalisation on them 5. Calculate the range and velocity of the targets in Equations ( 47) and ( 48 17. Find the maximum value and record R k , v k 18.…”
Section: Algorithm 1 the E-w Algorithmmentioning
confidence: 99%
“…A two‐stage method for multi‐target range and velocity estimation based on OFDM passive radar is proposed in [16], requiring multiple receivers. A modulation symbol‐domain method combined with sparse representation (SR) for range‐Doppler estimation is introduced in [17]. However, its random subcarrier allocation mechanism reduces the communication rate.…”
Section: Introductionmentioning
confidence: 99%
“…Although in radio frequency (RF) front-end architectures, both the radar and communication become similar, operating radar and communication simultaneously cause a series of problems such as the number of antennas, the energy consumption, and electromagnetic signal interference. So the concept of joint radar-communication (JRC) is proposed in the recent few decades, which enables radar and wireless communication users working in the same frequency band, sharing the same antenna resources, implementing radar sensing, and communication transmission synchronously [3][4][5][6][7][8]. A typical JRC is illustrated in Figure 1, it is shown that the JRC signal is sent from the radar transmitter, and the communication and radar are operated simultaneously.…”
Section: Introductionmentioning
confidence: 99%